THE INFLUENCE OF ARISTOTLE'S PERIPATHETIC PHILOSOPHY METHOD ON THE COGNITIVE ACHIEVEMENTS OF EARLY CHILDREN - Enjang Enjang; Enan Kusnandar; Heni Nopiyanti; Nita Adiyanti (Universitas Panca Sakti Bekasi, 2024)
By using the method of Aristotle's peripatetic philosophy, researchers are trying to determine the development of increased cognitive intelligence in early childhood if this method is implemented in learning. In describing the data obtained and the phenomena that occurred, the researcher used a descriptive qualitative method through a phenomenological approach, the researcher even went directly into the field as a key instrument. So that the results obtained are truly valid. The results of the research showed that of the 45 respondents consisting of teachers, students and parents, all of them showed that this method was very effective, in students there was an increase in cognitive intelligence, especially their sensitivity in using rationality. This shows that implementing Aristotle's peripatetic philosophical theory in early childhood learning will be able to make students more open-minded and more rational in learning.